Green finance and the mitigation of corporate debt financing in China: evidence and implications for sustainable finance - Fu, Quan’An (Frontiers in Environmental Science, 2024)
To address the pressing challenges posed by environmental issues, numerous countries have been actively exploring green finance practices. Using a sample of listed companies in China from 2008 to 2020, this study aims to enrich the understanding of the economic consequences of green finance. Specifically, it is the first to investigate the causal relationship between green finance and corporate debt financing levels. Our findings reveal that green finance effectively mitigates corporate debt financing levels, and this conclusion remains robust after undergoing a series of rigorous tests. Further analysis reveals that green finance achieves this by alleviating financing constraints and enhancing executive compensation. Heterogeneity analysis demonstrates that the impact of green finance is particularly pronounced in state-owned enterprises, regions with lower marketization levels, superior industrial structures, and lower carbon emissions. Additionally, our research shows that with the strengthening of external environmental regulations, green finance significantly promotes the reduction of long-term debt financing levels but has no significant impact on short-term debt financing levels. The conclusions of this study provide valuable insights for policymakers and enterprises seeking to reduce corporate debt financing levels. Moreover, it offers a new perspective on the economic consequences of green finance, particularly in the context of debt financing.